Pengaruh Media Sosial Dan Self Efficacy Terhadap Keberhasilan Usaha: Studi Kasus Pada Pelaku UMKM Desa Pelanggiran Laut Tador - Sari, Ayu Puspita; Siahaan, Rumiris; Napitu, Resna (Digital Business Progress, 2024)
The purpose of this study was to examine the effect of (1) social media on business success (2) self-efficacy on business success (3) social media and self-efficacy simultaneously on business success. This study uses a quantitative research approach. The population in this study is the UMKM actors in Pelanggiran Laut Tador Village, totaling 30 UMKM actors. The sampling technique uses saturated sampling technique which makes all members of the population as research samples. Methods of data collection using a questionnaire. Analytical tools: instrument test, classical assumption test, multiple linear regression analysis, t-test and f-test using SPSS version 25. The results of this study indicate that social media partially has no effect on business success, self-efficacy partially affects business success and based on the simultaneous results that social media and self-efficacy influence business success.